Saving endangered birds : ensuring a future in the wild - Maynard, Thane (New York : F. Watts, 1993)
Text and photographs examine the physical characteristics and habits of various endangered birds and discuss efforts to save them from extinction.
Includes bibliographical references and index.
Booklist.
Library Talk.
6.9
5-7.
5-8
Keywords: Birds -- Conservation -- Juvenile literature; Rare birds -- Juvenile literature; Birds -- Protection; Rare birds; Wildlife conservation; Birds -- Protection; Rare animals; Wildlife conservation